Design and Testing of A Sampling Plan for Two Continuous Production Lines - Mayureesawan*, Tidadeaw; Na Ayudthya, Prapaisri Sudasna (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
This paper presents a plan CSP-1-2L for inspection of two continuous production lines. The plan is defined by 2 numbers i1 and i2 (the numbers of consecutive non-defective units that must be produced on lines 1 and 2 during a 100% inspection of the lines) and 2 fractions f1 and f2 (the specified sampling frequencies for lines 1 and 2 during a fractional inspection of the lines). CSP-1-2L computes 3 performance measures, average total fraction inspected, average total outgoing quality and average total outgoing quality limit, for given values of incoming fractions of defective units on line 1 (p1) and on line 2 (p2). The validity and accuracy of the performance measure formulas for four inspection patterns have been tested by extensive simulations. Optimal inspection patterns have been found for the sets of p1, p2, i1, i2, r1(=1/f2) values for which the formulas are valid. For low levels of incoming fractions of defectives p1 and p2, the formulas for all performance measures are valid for all inspection patterns. However, for higher levels of p1, p2, or for large differences between them, the formulas are valid only for a restricted range of i1, i2, r1, r2 values. Further, if p1 < p2 then we must use i1 ≤ i2 and r1 < r2, and if there is a large difference between p1 and p2, then there must also be large differences between i1 and i2 and between r1 and r2. Keywords: Continuous sampling plan, Continuous production lines. Corresponding author: E-mail: g4585017@ku.ac.th and fengpsa@ku.ac.th